Traditional uses of some medicinal plants in Malatya (Turkey) - Tetik, Figen; Civelek, Semsettin; Cakilcioglu, Ugur (Elsevier Ireland Ltd, 2013)
Ethnopharmacological relevance: This study has identified not only the wild plants collected for medical purposes by local people of Malatya Province in the Eastern Anatolia Region, but also the uses and local names of these plants. It tried to provide a source for researchers studying in ethnobotany, pharmacology and chemistry by comparing the information obtained from traditionally used herbs with previous laboratory studies. Aim of the study: : In Turkey, use of plants for medical purposes has been a tradition. This study aims to identify wild plants collected for medical purposes by the local people of Malatya Province, located in the Eastern Anatolia Region of Turkey, and to establish the uses and local names of these plants. Materials and methods: A field study had been carried out for a period of approximately 2 years (20102011). A questionnaire was administered to the local people, through face-to-face interviews. During this period, 330 vascular plant specimens were collected. Demographic characteristics of participants, names of the local plants, their utilized parts and preparation methods were investigated and recorded. The plant species were collected within the scope of the study; herbarium materials were prepared; and the specimens were entitled. In addition, the relative importance value of the species was determined and informant consensus factor (FIC) was calculated for the medicinal plants included in the study. Results: In the area of research, 132 individuals who had knowledge about plants were interviewed. Mean age of the respondents was 44 years (in 35-73 years range). 108 plants were found to be used for medical purposes before in the literature analysis of the plants used in our study, while 15 plants were found to have no literature records. The most common families are: Asteraceae (21 plants), Lamiaceae (14 plants), and Rosaceae (12 plants). Local people were recorded to use the aerial parts, branches, flowers, fruits, latex, leaves, matured fruits, peduncle, resin, rhizomes, root bark, roots, seeds and style of the plants. Besides, it was observed that they dried and stored plants in unfavorable seasons in order to use them later. The medicinal uses of Heracleum antasiaticum Manden., Pimpinella olivieroides Boiss. & Hausskn., Scandix iberica Bieb., Taraxacum hybernum Stev., Tripleurospermum transcaucasicum (Manden.) Pobed., Cerastium chlortfolium Fisch. & Mey., Andrachne telephioides L, Euphorbia dendculata Lam., Astragalus cephalotes Banks. & Sol. var. brevicalyx Eig., Geranium ibericum Cav., Cyclotrichium nivenum (Boiss.) Manden. & Scheng., Salvia syriaca L., Popover arenarium Bieb., Dactylis glomerata L., Polygonum arenarium Waldst. & Kit. that we found were used in our study area and recorded for the first time. No information could be obtained regarding the names of eight wild plants that are being used in Malatya. In Turkey, local plant names display differences especially due to ethnographic reasons. The plants used in Malatya are known by the same or different local names in various parts of Anatolia. Our research area also includes people with Kurdish and Zaza ethnic origins. The respondents of the questionnaire are Turkish citizens. Conclusion: These plants are used in the treatment of many diseases. Comparison of the data obtained in this study from derived the plants growing in Malatya with the experimental data obtained in previous laboratory studies proved ethnobotanical usages to a great extent. Literature review indicated that curative plants that grow in Malatya are used in different parts of the world for the treatment of the same or similar diseases. These plants, used for the treatment of many varying diseases, are abundantly found in this region. Drying enabled local people to use medicinal plants in every seasons of the year. The plant flora of Malatya is threatened by such factors as grazing, expansion of new agricultural lands, and unsustainable picking of plants to generate income. Steps should be taken immediately to ensure the inclusion of relevant flora within conservation designations. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Ethnobotany; Medicinal plants; Traditional remedies; Use value; Informant consensus; Factor; Malatya